Perbedaan Kedudukan Perempuan Dan Laki-Laki Dalam Pandangan Fiqih - Ariyanto, Ariyanto; Wulandari, Siti; Dwi Saputri, Indah; Sajdah, Meilisa (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2024)
Seeing global developments and culture, women have been positioned as the common people of men. Indonesia, as a country whose majority population is Muslim, is therefore appropriate to provide special protection for women to carry out activities in public as long as they do not forget their duties as women. This research uses a descriptive quantitative method with research subjects of female and female students from the Asshidqu Kuningan Islamic boarding school with a population of 50 and a sample of 25 where data was collected using observation and questionnaires. The results of observations and questionnaires show that there are 30% of santri who work and 20% of santriwan who do the same work, then 15% of the sample of santriwan and 10% of the sample of santriwati. So the activities of santriwan and female students at the Asshidqu Islamic boarding school are almost the same.